Artificial intelligence-based analysis of time-lapse images of sphere formation and process of plate adhesion and spread of pancreatic cancer cells - Shichi, Yuuki; Gomi, Fujiya; Hasegawa, Yasuko; Nonaka, Keisuke; Shinji, Seiichi; Takahashi, Kimimasa; Ishiwata, Toshiyuki (Frontiers in Cell and Developmental Biology, 2023)
Background: Most pancreatic cancers are pancreatic ductal adenocarcinomas (PDAC). Spherical morphology formed in three-dimensional (3D) cultures and the effects of anticancer drugs differ between epithelial and mesenchymal PDAC cell lines. In the human pancreas, cancer cells form 3D tumors, migrate to adjacent tissues, and metastasize to other organs. However, no effective methods exist to examine the ability of the tumor mass to migrate to surrounding tissues in vitro. We used spheres formed in 3D culture to investigate whether the migratory ability of tumors of PDAC cell lines, including epithelial and mesenchymal cell lines, varies.Methods: Sphere formation and adhesion and spread on culture plates were examined by artificial intelligence-based analysis of time-lapse imaging using five epithelial and three mesenchymal PDAC cell lines. Fused and non-fused areas of the sphere surface during sphere formation on low-attachment plates, the adhesion area to normal culture plates, and the sphere area maintaining its original form during adhesion to plates were measured.Results: Immunocytochemical staining confirmed that E-cadherin was highly expressed in epithelial PDAC spheres, as was vimentin in mesenchymal PDAC spheres, in 2D culture. When forming spheres using low-attachment plates, most epithelial PDAC cell lines initially showed decreased sphere area, and then the covering cells fused to form a smooth surface on the sphere. Mesenchymal PANC-1 and MIA PaCa-2 cells showed little reduction in sphere area and few areas of sphere surface fusion. When formed PDAC spheres were seeded onto normal culture plates, spheres of epithelial PK-8 cells-which have the highest E-cadherin expression, form numerous cysts, and have smooth sphere surfaces-did not adhere to normal plates even after 60 h, and epithelial PK45-P and T3M-4 spheres hardly adhered. Conversely, the area of adhesion and spread of mesenchymal PANC-1 and KP4 cell spheres on normal plates markedly increased from early on, forming large areas of attachment to plates.Seeding spheres formed in 3D culture onto culture plates can clarify differences in tumor migration potential to surrounding areas. The masses formed by each PDAC cell line varied in migratory ability, with mesenchymal PDAC masses being more migratory than epithelial PDAC masses.